The Impact of Health Care Restructuring on Nosocomial Infections and Transmission of Antimicrobial Resistant Organisms - J Conly; Lynn Johnston (Canadian Journal of Infectious Diseases)
The past decade has seen a dramatic change in Canadian health care as the treatment of many patients shifts from the hospital setting to the home or other alternative health care settings (1). Complex advances in technology and significant changes in the funding environment have also precipitated many changes in the functional capacity of our health care system. The portion of the total Canadian health care expenditures that has been allocated to hospitals and other institutions has declined steadily over the past two decades (2,3). This reduction in institutional-based funding reflects the need to develop a system that improves the use of out-of-hospital sites for delivery of health care services and decreases reliance on the specific institutional component of the health care sector. Recent data reveal that Canadian hospital discharge rates have decreased by 14% between 1994 and 1998, and there has been a reduction in the length of stay from 7.4 to 7 days (4). In conjunction with a reduction in the number of hospital beds, there has been a massive shift in the proportion of surgeries that are performed on an outpatient basis. Further developments in the delivery of care include the increased use of telehealth, which allows health care professionals to provide increasingly complex services centralized hospital sites to outlying areas.